2004
DOI: 10.1007/bf03395472
|View full text |Cite
|
Sign up to set email alerts
|

Functional Cues for Position Learning Effects in Animals

Abstract: Using transfer methodology, several possible factors that could have affected the expression of serial position learning were examined with runway-trained rats. A 3-trial series (8NP)-for which 8 and P refer to series trials when sucrose (8) and plain (P) Noyes pellets were used as a reward , and N refers to a trial without reward-was the basis for training in the first 2 and final experiments. Transfer tests in Experiment 1 altered reward memories , the time between trials in the series , or both . Tests in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
(42 reference statements)
1
4
0
Order By: Relevance
“…This is an interesting finding considering other literature that suggests rats do use serial position as a cue (Burns, Dunkman, Jr., & Detloff, 1999; Burns, Johnson, Harris, Kinney, & Wright, 2004; Burns, Kinney, & Criddle, 2000). Burns et al (2000) trained two groups of rats on 3-trial series in which the first two trials consisted of rewards while the third trial was not rewarded.…”
Section: Methodssupporting
confidence: 67%
“…This is an interesting finding considering other literature that suggests rats do use serial position as a cue (Burns, Dunkman, Jr., & Detloff, 1999; Burns, Johnson, Harris, Kinney, & Wright, 2004; Burns, Kinney, & Criddle, 2000). Burns et al (2000) trained two groups of rats on 3-trial series in which the first two trials consisted of rewards while the third trial was not rewarded.…”
Section: Methodssupporting
confidence: 67%
“…First, in the present study, no differential feedback, exteroceptive or proprioceptive, followed a response. In contrast, previous studies have used procedures in which list items are associated with different quantities of food and/or different spatial locations (e.g., Burns, Johnson, Harris, Kinney, & Wright, 2004; Olthof & Santi, 2007). When differential outcomes follow responses, it is essentially impossible to determine if the functional stimulus for a response is the outcome associated with an item or the item's ordinal position.…”
Section: Discussionmentioning
confidence: 99%
“…If their rats had learned position in the PSN series, approach would have been slow on the S trial of the PPSN transfer series because that position was never rewarded in training. Using similar training methods, however, with initial training on an SNP series, Burns et al (2004) found slow approach on the second trials of NP and SSNP transfer series. One possibility entertained by Capaldi et al (1997) was that position learning requires extensive training, but reward-memory learning occurs rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence so far suggests that both kinds of learning may occur and probably do occur, even if one overshadows the other. They are not mutually exclusive (Burns, Johnson, Harris, Kinney, & Wright, 2004). The blocking procedure should foster a better understanding of how one type of association moderates the other.…”
mentioning
confidence: 99%